Development of an Assessment Tool for Prioritizing Influencing Factors of Sustainability in Higher Education - Jungthawan, Siripong; Tiyarattanachai, Ronnachai (My University, 2020)
The United Nations set 17 Sustainable Development Goals (SDGs) in August 2015 as a blueprint to achieve sustainable future for all nations at all levels. Higher education institutions are expected to significantly contribute to the goal, as they must produce the human resources and research necessary for achieving sustainability. In October 2019, Times Higher Education (THE) launched the THE University Impact Rankings, which encouraged universities to focus efforts that pose positive impacts on SDGs in the areas related to the university's operation. Since SDGs and their targets may have different priorities in different countries, we examined the perspectives of stakeholders in 16 Thai universities ranked in the THE World University Rankings to prioritize the SDG areas on which the universities should focus. We expect that this study will be used by Thai university executives to optimize resources spent on achieving better sustainability performance.
Keywords: Higher education; Higher Education Institution (HEI); Sustainability in Higher Education (SHE); Sustainable Development Goals (SDGs); University Impact Ranking